Primary palliative care education in emergency medicine residency: A mixed‐methods analysis of a yearlong, multimodal intervention. Issue 6 (20th December 2022) - Benesch, Tara D.; Moore, Justin E.; Breyre, Amelia M.; DeWitt, Raizel; Nattinger, Caroline C.; Dellinger, Elaine; Anderson, Erik S.; Bulman, Linda
Abstract: Background: Emergency medicine (EM) physicians frequently care for seriously ill patients at the end of life. Palliative care initiated in the emergency department (ED) can improve symptom management and quality of life, align treatments with patient preferences, and reduce length of hospitalization. We evaluated an educational intervention with digital tools for palliative care discussions in an urban EM residency using the reach, effectiveness, adoption, implementation, and maintenance (RE‐AIM) framework. Methods: Our intervention, conducted from July 2020 to August 2021, included education on palliative care techniques, digital tools, and incentives for participation. We tracked goals of care conversations and palliative care consults using electronic medical record data, conducted pre‐ and posttraining surveys, and used semistructured interviews to assess resident perspectives on palliative care conversations in the ED. Outcomes included number of goals of care conversations recorded by EM residents, consults to palliative care from the ED, and resident perspectives on palliative care in EM. Results: The results were as follows: reach —45 residents participated in the intervention; effectiveness —89 goals of care conversations were documented by 23 ED residents, and palliative care consults increased from approximately four to 10 monthly; adoption —over half the residents who participated in the intervention documented goals of care discussions using an electronic dotphrase; implementation —by the completion of the intervention, residents reported increased comfort with goals of care conversations, saw palliative care as part of their responsibility as EM physicians, and effectively documented goals of care discussions; and maintenance —at 2‐month follow up, palliative care consults from the ED remained at approximately 10 monthly, and digital tools to prompt and track palliative care discussions remained in use. Conclusions: An integrated palliative care training for EM residents with technological assists was successful in facilitating goals of care discussions and increasing palliative care consults from the ED.